Aplicação de ultrassons no deslocamento de petróleo em meio poroso - Santos, Joselisse Soares de Carvalho (2010)
The objective of this study was to evaluate the displacement of petroleum/diesel solutions, at different concentrations, observing the effect of ultrasonic vibrations in fluids present in porous media to obtain an increase in oil production. The bubbles produced by ultrasound implode asymmetrically in the rock, generating liquid jets with high speed, displacing the oil present in porous media. The oil/diesel solutions were prepared with concentrations ranging from 20 g/L to 720 g/L in oil in relation to diesel and its viscosities were obtained in a Brookfield Rheometer RS2000, with temperature ranging from 25 to 55 °C. After, calculations were performed to obtain the activation energy data for oil/diesel solutions. For oil recovery experiments, cylindrical samples of porous rock (core samples), with resin around the perimeter and its two circular bases free to allow the passage of fluids, were first saturated with 2% KCl solution and after with oil solutions. The results of oil extraction were satisfactory for all studied solutions, being obtained up to 68% partial displacement with saline solution injection. The ultrasound system was used after saline injection, increasing oil displacement, with oil extractions ranging from 63% to 79%. During the experiments, it was observed the warming of core samples, helping to reduce the viscosity of more concentrated systems, and consequently enhancing the percentage of advanced recovery for all studied solutions